Politically Induced Metonymy in George Orwell’s “Nineteen Eighty-Four” - Kopczyk, Katarzyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The following article attempts to analyse the phenomenon of conceptual metonymy occurring in George Orwell’s novel “Nineteen Eighty-Four”. The analysis involves only a few examples of metonymy related to the conceptual domain of POLITICS. The article postulates that politics, in general, evokes negative associations. Thus, one of the objectives is to verify whether in majority of examples, political activity connotes adverse and unfavourable feelings. Moreover some concepts being part of metonymy have been evaluated according to the way in which they are perceived by English speakers. The article comprises two parts. The theoretical part contains a brief outline of Cognitive Linguistics and metonymy, as well as a short description of political reality in “Nineteen Eighty-Four”, which is essential to understand the context of analysed linguistic expressions. The second part involves the analysis proper of the material gathered. Four metonymies describing relations between people and the world in which they live have been formulated and examined.
Keywords: cognitive linguistics; conceptual metonymy; Orwell; Nineteen Eighty-Four; politics